Monitoring the impact of COVID-19 in Myanmar: Mechanization service providers - December 2020 survey round - Takeshima, Hiroyuki; Zone, Phoo Pye; Win, Myat Thida; Masias, Ian (International Food Policy Research Institute, 2021)
Mechanization service providers (MSP) in Myanmar were originally interviewed by telephone in May, June, July, and November 2020, covering mostly combine-harvester SPs (CHSP) and tractor SPs (TSP), to determine how their businesses were being affected by COVID-19 related restrictions. The results of those surveys were published in Myanmar Strategy Support Program Notes 07, 12, 17, and 39, respectively. To trace the continuing impact of the COVID-19 pandemic on their economic activities, a fifth phone survey of MSPs was done in mid-December 2020, administered mostly to SPs in harvesting activities. This reports on the results of the fifth survey, as well as on some trends from the earlier surveys.